The origins of the Cuban Revolution of 1959 - Salim Lamrani (Études Caribéennes)
Coveted from the beginning of the 19th century by the United States who wanted to annex it to their territory, Cuba lived under the constant threat of seeing its aspiration for independence questioned by the powerful neighbor who denied them the right to a sovereign existence. After the military intervention of 1898 and the occupation of the island, Washington in one way or another exerted a more or less direct influence over all aspects of Cuban society, thereby gaining control over its natural resources. The origins of the 1959 Cuban Revolution led by Fidel Castro lie in the turmoil of this tormented history, between aspiration for independence and subjection.